Isolation of Multi Drug Resistant MRSA from Cattle in Mizoram - Debbarma, Binipi; Rajesh, J. B.; Ralte, Lallawmzuali; Debnath, Ankita; Lucy, Elone; Kar, Payel (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during January to March, 2023 at College of Veterinary Sciences and Animal Husbandry, Selesih, Aizawl, Mizoram to investigate and isolate MDR S. aureus from cattle in Mizoram. Nasal swab samples collected from cattle and inoculated in nutritional broth. Then samples were streaked on Baird Parker Agar (BPA) media plates and positive isolates were streaked on the Mannitol Salt Agar (MSA). The yellow colonies were coagulase-positive cocci and Staphylococci were recognized as gram-positive cocci by the Gram’s staining technique. Suspicious colonies were placed into the nutrient broth tubes and cultured. Catalase test was performed for the confirmation of Staphylococci along with standard biochemical verifications. All the phenotypically validated S. aureus isolates were kept in nutritional agar, as well as in Luria Bertani (LB) broth for genotypic confirmation. MHA agar was used for the antimicrobial sensitivity test (Methicillin, Sulfafurazole, Cefotaxime, Clindamycin, and Doxycycline) . Isolates were subjected to PCR to detect the presence of the mecA, and femA genes responsible for MRSA. In this study, 19.05% (8/42) of nasal swab samples were showing the presence of S. aureus. The overall percentage of MRSA was found to be 7.14% (3/42). Anti-microbial sensitivity test using different antibiotics revealed MDR S. aureus in samples collected from cattle. The genes specific for the MRSA i.e., mecA and femA could be detected in PCR that is responsible for the virulence of MDR S. aureus. This report dealt with the development and possible transmission of MDR S. aureus in cattle population of the region.